Application of a three‐dimensional visualization model in intraoperative guidance of percutaneous nephrolithotomy. (11th May 2022) - Wang, Lei; Zhao, Zichen; Wang, Gang; Zhou, Jianfang; Zhu, He; Guo, Hongfeng; Huang, Huagang; Yu, Mingchuan; Zhu, Gang; Li, Ningchen; Na, Yanqun
Abstract : Objectives: To establish a three‐dimensional visualization model of percutaneous nephrolithotomy, apply it to guiding intraoperative puncture in a mixed reality environment, and evaluate its accuracy and clinical value. Methods: Patients with percutaneous nephrolithotomy indications were prospectively divided into three‐dimensional group and control group with a ratio of 1:2. For patients in three‐dimensional group, positioning markers were pasted on the skin and enhanced computed tomography scanning was performed in the prone position. Holographic three‐dimensional models were made and puncture routes were planned before operation. During the operation, the three‐dimensional model was displayed through HoloLens glass and visually registered with the patient's body. Puncture of the target renal calyx was performed under three‐dimensional‐image guiding and ultrasonic monitoring. Patients in the control group underwent routine percutaneous nephrolithotomy in the prone position under the monitoring of B‐ultrasound. Deviation distance of the kidney, puncture time, puncture attempts, channel coincidence rate, stone clearance rate, and postoperative complications were assessed. Results: Twenty‐one and 40 patients were enrolled in three‐dimensional and control group, respectively. For three‐dimensional group, the average deviation between virtual and real kidney was 3.1 ± 2.9 mm. All punctures were performed according to preoperative planning. Compared with the control group, the three‐dimensional group had shorter puncture time (8.9 ± 3.3 vs 14.5 ± 6.1 min, P < 0.001), fewer puncture attempts (1.4 ± 0.6 vs 2.2 ± 1.5, P = 0.009), and might also have a better performance in stone clearance rate (90.5% vs 72.5%, P = 0.19) and postoperative complications ( P = 0.074). Conclusions: The percutaneous nephrolithotomy three‐dimensional model manifested acceptable accuracy and good value for guiding puncture in a mixed reality environment.